KINERJA PEGAWAI DI KANTOR DESA PAL IX KECAMATAN SUNGAI KAKAP KABUPATEN KUBURAYA - Eka Purwanti E.21110012 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Phenomena related to performance issues that show is not maximized. It is seen from the three indicators, namely the aspect of quality, quantity, and timeliness. The quality is not yet optimal on the look of the lack of infrastructure facilities and prasaranya, on the quantity / number of employees or the number of human resources is said to be less so that the work becomes hampered. Furthermore, the timeliness of completion of the work can not be said to be good, the factors that influence still remains associated with such a lack of personnel or employee because of the number of employees that a little can not finish the work on time. The purpose of this study was to determine the performance of employees at Pal Village Office IX Sungai Kubu Raya snapper. In this study, researchers used performance indicators proposed by Agus Dharma (2003: 355), which consists of three indicators of quality, quantity, and timeliness. The study was a descriptive study with a qualitative approach. The results of this study indicate that there is still a quality of an individual's ability to inhibit quality deficiencies that ultimately affect performance at the Village Office Pal IX, Quantity / number of employees or the number of human resources are lacking thus making the performance is still not optimal, and Timeliness in a number of tasks and functions are still low so the impact on performance is still not optimal. Timeliness in completion of the work will also affect the assessment of the performance of an organization. Finally, the researchers provide recommendations to the Village Office Pal IX Sungai Kubu Raya snapper is expected to further increase human resources, improve education and skills possessed, as well as improving facilities and infrastructure, that are expected to work effectively and better and be able to run duties and functions properly.Keywords: employee performance, quantity, quality, and timeliness.